Predictive factors of mortality in granulomatosis with polyangiitis: A single-center study - Müge Aydın Tufan; Nihan Tekkarışmaz (Archives of Rheumatology, 2021)
Objectives: The aim of this study was to identify predictors of mortality in granulomatosis with polyangiitis (GPA) patients and to seek the ways of improving survival in GPA patients. Patients and methods: Between January 2005 and June 2020, a total of 60 patients (26 males, 34 females; median age: 49 years; range, 19 to 75 years) who were diagnosed with GPA were retrospectively analyzed. Demographic, clinical, laboratory, and radiological findings of all patients were recorded. Survival rates were analyzed using the Kaplan-Meier plot. Results: The median follow-up was 36 months, and 10 (16.7%) patients died during the study period. Univariate analysis showed that the prognostic values were attributed to high serum creatinine levels (>2.1 mg/dL; p=0.01), proteinuria (p=0.01), dialysis-requiring renal damage at the time of diagnosis (p=0.01) or at any time during follow-up (p=0.01), low lymphocyte levels (p=0.01), hypoalbuminemia (p=0.04), absence of upper respiratory tract involvement (p=0.01), presence of lung involvement with cavitary lesions (p=0.01), high Birmingham Vascular Activity Score (p=0.02), and history of serious infection (p=0.01). In the multivariate analysis, the presence of renal damage requiring dialysis at any time during follow-up (relative risk [95% confidence interval]: 21 [4.1-18.3]; p=0.01) was found to be an independent predictor of mortality. Immunosuppressive drugs exerted no effect on mortality, and the most common causes of death were infections (50%). Conclusion: The presence of dialysis-requiring renal damage is the most important risk factor for mortality in GPA patients. These patients should be followed more closely and carefully to improve survival.